PENGEMBANGAN POTENSI SUMBER DAYA ALAM FOSIL KAYU DI DAERAH GORONTALO - Sunarty Suly Eraku; Aang Panji Permana; Evi Hulukati (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2017)
Gorontalo area is part of the arc volcano - plutonic North Sulawesi predominantly volcanic rocks and intrusif rock Eocene to Quaternary. The tectonic position makes the Gorontalo area of natural resource mining prospects both metallic and non metallic minerals. One of them is a non-metal potential of petrified wood. The purpose of this study to analyze the condition of geomorphology, lithology, stratgraphy, and determine the nature of the physical characteristics of petrified wood in order to formulate feasibility as gemstones. The method used qualitative and quantitative results of the field survey which is then compiled the results of the laboratory. Field analysis in the form of geological mapping, sampling and documentation of geological data. The laboratory analysis conducted mineralogical and geochemistry analysis in the form of X-Ray Diffraction (XRD) and X-Ray Fluorescence (XRF). Dissemination of research results, the petrified wood in Tohupo River and Molannihu River. Petrified wood found in fluvial and alluvial sediment in tuffaceous sandstone layer with two types of  insitu and transported. Results of laboratory analysis both mineralogy and gochemistry indicates that the mineral constituent of petrified wood are Quartz (SiO2) with good quality so worty as a gemstone because of its aesthetic, translucent and hardness 7 Mohs Scale.